Media Influence on Women’s Lifestyle: A Pathological Analysis - Amiri, Shirzad (Psychology of Woman Journal, 2023)
In the current era, with the emergence of new communication and information technologies and new media, we are witnessing profound changes in the lifestyle and culture of different societies, and today, the media are an indispensable part of human life. Media serve as a conduit for transmitting the heritage and culture of past generations to future ones and are considered one of the primary tools of cultural imperialism against other cultures, and change and evolution in various cultures can be shaped through the media. Alongside this, in the present century, we are witnessing fundamental changes in various perspectives and discourses regarding women. Nowadays, women play an influential role in societies, and any changes in women’s thinking, attitudes, and behavior lead to changes in family culture and subsequently in societal culture. Therefore, we are witnessing changes in women’s lifestyle. Undoubtedly, the changes observed in women’s lifestyle in society are not unaffected by media content and messages. Researchers in the field of media and communication believe that media contribute to the process of identity formation and meaning-making, and they influence the behavioral patterns, social conduct, and public norms in society. Thus, media significantly contribute to shaping the intellectual and theoretical system of influential individuals, and ultimately, it is this intellectual system that determines the foundations of lifestyle. This article delves into the pathological analysis of the impact of media on women’s lifestyle.